CD36 Enhances Vascular Smooth Muscle Cell Proliferation and Development of Neointimal Hyperplasia. Issue 2 (February 2019) - Yue, Hong; Febbraio, Maria; Klenotic, Philip A.; Kennedy, David J.; Wu, Yueheng; Chen, Shaoxian; Gohara, Amira F.; Li, Oliver; Belcher, Adam; Kuang, Bin; McIntyre, Thomas M.; Silverstein, Roy L.; et al.
Abstract : Objective—: Dysregulated proliferation of vascular smooth muscle cells (VSMC) plays an essential role in neointimal hyperplasia. CD36 functions critically in atherogenesis and thrombosis. We hypothesize that CD36 regulates VSMC proliferation and contributes to the development of obstructive vascular diseases. Approach and Results—: We found by immunofluorescent staining that CD36 was highly expressed in human vessels with obstructive diseases. Using guidewire-induced carotid artery injury and shear stress–induced intima thickening models, we compared neointimal hyperplasia in Apoe −/−, Cd36 −/− /Apoe −/−, and CD36 specifically deleted in VSMC (VSMC cd36 −/− ) mice. CD36 deficiency, either global or VSMC-specific, dramatically reduced injury-induced neointimal thickening. Correspondingly, carotid artery blood flow was significantly increased in Cd36 −/− /Apoe −/− compared with Apoe −/− mice. In cultured VSMCs from thoracic aorta of wild-type and Cd36 −/− mice, we found that loss of CD36 significantly decreased serum-stimulated proliferation and increased cell populations in S phase, suggesting that CD36 is necessary for VSMC S/G2-M-phase transition. Treatment of VSMCs with a TSR (thrombospondin type 1 repeat) peptide significantly increased wild-type, but not Cd36 −/− VSMC proliferation. TSR or serum treatment significantly increased cyclin A expression in wild-type, but not in Cd36 −/− VSMCs. STAT3 (signal transducer and activator of transcription), which reportedly enhances both VSMC differentiation and maturation, was higher in Cd36 −/− VSMCs. CD36 deficiency significantly decreased expression of Col1A1 (type 1 collagen A1 chain) and TGF-β1 (transforming growth factor beta 1), and increased expression of contractile proteins, including calponin 1 and smooth muscle α actin, and dramatically increased cell contraction. Conclusions—: CD36 promotes VSMC proliferation via upregulation of cyclin A expression that contributes to the development of neointimal hyperplasia, collagen deposition, and obstructive vascular diseases. Abstract : Supplemental Digital Content is available in the text.